Analisis Pendekatan Permisif dan Pendekatan Buku Masak dalam Manajemen Kelas: Studi Hasil Wawancara dengan Guru - Anisa Anisa; Assyfaturrahmah Assyfaturrahmah; Rizki Suwandi; Umi Hasnah; Zumi Nur Faiza; Zhidan Muhammad Elfarizi; Ade Irma (Pusat Riset dan Inovasi Nasional, 2026)
Classroom management is an important aspect of creating a conducive learning environment and supporting the achievement of learning objectives. This study aims to analyze the permissive approach and the cookbook approach in classroom management based on the results of an interview with a teacher. The research employed a descriptive qualitative method, with interviews used as the primary data collection technique. The findings indicate that the teacher does not fully implement either the permissive approach or the cookbook approach. The teacher provides students with freedom within limits that support the learning process while still enforcing agreed-upon classroom rules. In addition, the teacher does not rely on rigid procedures but instead adapts classroom management strategies to students' characteristics and the situations encountered in the classroom. The study reveals that the teacher tends to adopt an adaptive classroom management approach by combining firmness, empathy, and flexibility, thereby creating an orderly, comfortable, and effective learning environment that supports the achievement of educational objectives.